Quality of Four-Tier Diagnostic Test on Wave and Vibration Materials: An Empirical Study Using Rasch Modeling - Sukarelawan, Moh. Irma; Indratno, Toni Kus; Oktova, Raden; Abdullah, Nurul Syafiqah Yap (Department of Physics, Faculty of Mathematics and Natural Sciences, 2024)
Not all teachers have the ability to develop diagnostic instruments for misconception. Meanwhile, there is an urgent need to diagnose student misconceptions. Therefore, this research aims to carry out the process of adapting misconception-diagnostic instruments to wave and vibration materials. This study used a cross-sectional quantitative survey method. The adaptation process was conducted with 306 state high school students taking wave and vibration classes. Respondents were selected using convenience sampling techniques. 4WADI (Four-tier Wave and vibration Diagnostic Instrument) was translated into Indonesian, consulted with language experts, and assessed by material and evaluation experts to produce an instrument appropriate to the Indonesian cultural context. Before the empirical test was carried out, I-4WADI (Indonesian et al. and vibration Diagnostic Instrument) was tested for readability on 35 students. As a result, the I-4WADI has excellent readability. The validation results of six experts were analyzed using the Aiken V technique. A total of 25 items were used for expert validation. Empirical validation data were analyzed using the Rasch model. Review empirical validation from the aspects of item fit and unidimensionality. The analysis results show that I-4WADI has good quality based on validity and reliability. The infit MnSq values ranged from 0.81 to 1.40, and the outfit MnSq values ranged from 0.71 to 1.36. The instrument reliability value is 0.98. So, I-4WADI can be applied to high school students in Indonesia. These findings have practical implications for teachers who wish to diagnose students' misconceptions about waves and vibration.